Predictors of coronary slow flow phenomenon in patients with angina and normal epicardial coronaries. (14th October 2021) - Maddali, V R; Nagula, P; Ravi, S; P, K M K
Abstract: Background: Coronary slow flow phenomenon (CSFP), also called as syndrome Y is characterized by the delayed passage of contrast distally when injected into the epicardial coronaries. It accounts for upto 7% of patients undergoing coronary angiogram (CAG) for angina. Conventionally, it is determined by the coronary filling time. We aimed to determine whether coronary emptying time is a significant predictor of the coronary slow flow. Purpose: To determine the coronary artery filling time and emptying time at prespecified vascular landmarks in patients with chest pain and normal epicardial coronaries. To determine the association of coronary arterial filling time and emptying time in patients with coronary slow flow phenomenon. To determine the association of various conventional coronary artery disease risk factors and various clinical parameters in patients with coronary slow flow phenomenon. Methods: Patients with angina, having normal epicardial coronaries on CAG were selected consecutively between January 2019 and December 2020. Each angiogram was assessed for the coronary filling and emptying times at prespecified standard vascular landmarks on the basis of TIMI frame counts (TFC). Results: A total of 37 patients with normal epicardial coronaries were analyzed, out of which 27 patients had slow flow in LAD and 17 patients had slow flow in RCA (10 had normal flow in LAD and 12 had normal flow in RCA). Eight had non dominant RCA, which were too small for analyzing TFC were excluded from the study. We observed positive correlation of coronary filling times and emptying times, both in LAD (R-Sq 0.24) and RCA (R-Sq 0.05) in slow flow patients unlike those with normal flow. We found the filling times and emptying times are significantly prolonged in slow flow patients [with mean CTFC values of 77.94 & 92.85 in LAD and 36.91 & 120.82 in RCA, respectively (P<0.05)]. The capillary and venous transit time is prolonged both in LAD and RCA slow flow groups, which was of statistical significance in the RCA slow flow group (P<0.05), but not in LAD slow flow group (P=0.43). We observed slow flow significantly more in male population (P=0.02) and associated with high LDL/HDL ratios and high triglycerides. Conclusion: 1. In addition to coronary artery filling times, Coronary artery emptying time is an independent and significant predictor of coronary slow flow phenomenon. 2. Capillary and venous transit time is significantly prolonged in patients with slow flow in RCA whereas in patients with LAD slow flow there is non significant prolongation of capillary and venous transit time. 3. There is a positive correlation of coronary emptying time with coronary filling time in Coronary Slow Flow. This correlation is not seen in patients with normal coronary flow. 4. Coronary slow flow is observed significantly more in male population. 5. Coronary slow flow is significantly associated with high LDL/HDL ratios and triglyceride levels. FUNDunding Acknowledgement: Type of funding sources: None.